The Relationship Between Low-Density Lipoprotein Cholesterol and Coronary Artery Calcium Score in Patients with Chronic Coronary Syndrome Without Diabetes Mellitus at RSUP Haji Adam Malik Medan - Muslim, Suci Asriri Pradina; Lubis , Hilfan Ade Putra; Nasution , Ali Nafiah (Journal of Society Medicine, 2025)
Introduction: Chronic Coronary Syndrome (CCS) is the most common symptom of ischemic heart disease and is a major cause of morbidity and mortality worldwide. One of the associated risk factors for coronary heart disease events is Low Density Lipoprotein Cholesterol (LDL-C) through the process of atherosclerosis. Computed Tomography Coronary Artery (CTCA) is an examination that can be performed to assess atherosclerotic plaques and Coronary Artery Calcium Score (CAC Score). This study was conducted to assess the relationship between LDL and CAC Score in CCS patients. Methods: This study is an observational analytical study involving 300 patients diagnosed with CCS during the period from March 1, 2023, to March 31, 2024, at RSUP H. Adam Malik Medan. All involved patients underwent LDL examination and CTCA examination as well as CAC Score measurement. Patient characteristics, disease history, and risk factors were also recorded. Results: There was a significant relationship between LDL levels and CAC Score (P value: 0.008; OR: 1.91 (CI: 1.184-3.1). Among the patient characteristics in this study, the strongest protective factor was female gender (P value: <0.01; OR: 0.228 (CI: 0.119-0.437)), and the strongest risk factor was patients with hypertension (P value: 0.017; OR: 1.97 (CI: 1.119-3.484). Conclusion: LDL can increase CAC Score in CCS patients.